1997
DOI: 10.1074/jbc.272.19.12257
|View full text |Cite
|
Sign up to set email alerts
|

Rho-associated Kinase Directly Induces Smooth Muscle Contraction through Myosin Light Chain Phosphorylation

Abstract: Small GTPase Rho plays pivotal roles in the Ca 2؉ sensitization of smooth muscle. However, the GTP-bound active form of Rho failed to exert Ca 2؉ -sensitizing effects in extensively Triton X-100-permeabilized smooth muscle preparations, due to the loss of the important diffusible cofactor (Gong, M. C., Iizuka, K., Nixon, G., Browne, J. P., Hall, A., Eccleston, J. F., Sugai, M., Kobayashi, S., Somlyo, A. V., and Somlyo, A. P. (1996) Proc. Natl. Acad. Sci. U. S. A. 93, 1340 -1345). Here we demonstrate the contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
429
1
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 540 publications
(444 citation statements)
references
References 25 publications
13
429
1
1
Order By: Relevance
“…Several investigators, including us, have demonstrated that there is a possible association of ROCK activity with oxidative stress and that smoking enhances the activation of ROCKs in vascular smooth muscle cells in vivo and in vitro. 98,109,112 These findings suggest a correlation between oxidative stress and ROCK activity in humans. Hernandez-Perera et al 113 showed that Rho is required for the basal expression of preproendothelin-1 in vascular endothelial cells, which gives rise to endothelin-1.…”
Section: Tetrahydrobiopterin (Bh 4 )mentioning
confidence: 67%
See 1 more Smart Citation
“…Several investigators, including us, have demonstrated that there is a possible association of ROCK activity with oxidative stress and that smoking enhances the activation of ROCKs in vascular smooth muscle cells in vivo and in vitro. 98,109,112 These findings suggest a correlation between oxidative stress and ROCK activity in humans. Hernandez-Perera et al 113 showed that Rho is required for the basal expression of preproendothelin-1 in vascular endothelial cells, which gives rise to endothelin-1.…”
Section: Tetrahydrobiopterin (Bh 4 )mentioning
confidence: 67%
“…ROCK activates myosin light-chain kinase by phosphorylation of the myosin-binding subunit in myosin light-chain phosphatase, leading to contraction of vascular smooth muscle cells. 97,98 Indeed, the RhoA/ROCK pathway has been shown to be involved in the formation of atherosclerotic lesions, vasoconstriction and myocardial hypertrophy and to be activated in patients with hypertension and in patients with coronary artery disease. [99][100][101][102][103][104] Recently, we have shown that FMD is an independent predictor of leukocyte ROCK activity in healthy men and men with cardiovascular risk factors but without established cardiovascular or cerebrovascular diseases, suggesting that cumulative cardiovascular risk, including aging and hypertension, may enhance ROCK activity and endothelial dysfunction.…”
Section: Tetrahydrobiopterin (Bh 4 )mentioning
confidence: 99%
“…Signaling through its effectors Rho kinase (ROCK) and mDia, Rho stimulates actin stress fiber formation by stimulating the monomeric actin binding protein profilin, and stabilizes stress fibers by inhibiting the activity of the actin depolymerizing protein, cofilin [35][36][37][38][39][40]. Bundling of actin filaments with myosin to form stress fibers, itself stimulated by ROCK and myosin light chain kinase, stimulates cell contraction and stabilization of focal adhesions [41][42][43][44], points of integrin-extracellular matrix contact between the ventral surface of the cell and the underlying substrate. Rho-mediated contractility is important for retraction of the cell rear and translocation of the cell body [26].…”
Section: Rho Family Gtpases Regulate Actin Dynamicsmentioning
confidence: 99%
“…Activation of Rho stimulates contractility and focal adhesion formation by promoting bundling of actin filaments and associated myosin motors into stress fibers [44]. Rho-ROCK signaling influences contraction through effects on both the myosin and actin: ROCK elevates myosin light chain phosphorylation by inhibiting myosin phosphatase and/or by directly phosphorylating myosin light chain (MLC) [41][42][43]. ROCK also phosphorylates and activates LIM kinase [64], which in turn phosphorylates and inactivates the actin severing protein, cofilin [36,65].…”
Section: Focal Adhesion Dynamicsmentioning
confidence: 99%
“…Phosphorylation of the myosin regulatory light chain (MLC 20 ) by MLCK allows the actin-myosin interaction to proceed with resultant ATP hydrolysis, crossbridge formation and force generation. 12 The sensitivity of the contractile process to [Ca 2+ ] i can also be influenced by contractile agonists, probably through modulation of myosin phosphatase activity 13 or by mitogen activated kinase (MAP kinase) dependent phosphorylation of thin filament proteins caldesmon and calponin, 14 and there is evidence that AII can enhance ␣ 1 -adrenoceptor mediated contraction in rabbit aorta by activation of protein kinase C (PKC). 15,16 Surprisingly AII has also been reported to induce a reduction in response to potassium in rabbit mesenteric arteries by a mechanism dependent on a transcriptional process.…”
Section: Intracellular Ca 2+ ([Ca 2+ ] I )mentioning
confidence: 99%